If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4x + -8x = 6x + -4 + 3 + -12 Combine like terms: x + 4x = 5x 5x + -8x = 6x + -4 + 3 + -12 Combine like terms: 5x + -8x = -3x -3x = 6x + -4 + 3 + -12 Reorder the terms: -3x = -4 + 3 + -12 + 6x Combine like terms: -4 + 3 = -1 -3x = -1 + -12 + 6x Combine like terms: -1 + -12 = -13 -3x = -13 + 6x Solving -3x = -13 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -3x + -6x = -13 + 6x + -6x Combine like terms: -3x + -6x = -9x -9x = -13 + 6x + -6x Combine like terms: 6x + -6x = 0 -9x = -13 + 0 -9x = -13 Divide each side by '-9'. x = 1.444444444 Simplifying x = 1.444444444
| 4(k-4)-3(k+2)-13=-29 | | 2x+2y=62 | | -210x+6y=330 | | -19a-12+4a=-57 | | -8x^2+14x=12 | | 3n+7-8n=34-11n+21 | | 3(3x+1)=-6 | | 10-5-3x-2x=0 | | -8x^2+14=-12 | | 18x^3-15x^2-7x= | | 2a^2-52-8a=32+a^2-3a | | -3x+2y-(7+x)+(x+7)= | | W=8g+700 | | 3(4+x)=-8(6-x) | | -4a+3-6a-8=15 | | -94=5(2m+2)-2m | | 9(y-1)-(y-5)=10 | | 2Y+4y-8y=36 | | 4p+yr=r-9f | | Y=8g+700 | | 6+4y+10=18 | | 2(4a+3)(a+1)=21 | | 2r-6-7r-9= | | 5(2p-4(p+5))=1 | | 4(3x+2)=200 | | 20x^3-11x^2-9x= | | 4(x+3)-4=8x+104x | | 6+3(b+4)=5b+(b-9) | | 3(1)-5y=0 | | x+8-3=4+3-5 | | 13+5b+7b=5b-7+2b | | (4x+4)(2x+9)= |